2018
DOI: 10.1002/lsm.23042
|View full text |Cite
|
Sign up to set email alerts
|

Clinical benefit of using a multifractional Er:YAG laser combined with a spatially modulated ablative (SMA) module for the treatment of striae distensae: A prospective pilot study in 20 patients

Abstract: Background and Objective: Striae distensae (SD) are cutaneous lesions that often occur on the breasts, abdomen, hips, and thighs. The aim of this study is to evaluate the effectiveness of a new technique using a non-invasive Er:YAG laser combined with Spatially Modulated Ablation (SMA) module for the treatment of SD. Study Design/Materials and Methods: This prospective pilot clinical study included 20 patients with skin phototypes I to IV who are affected by SD. The Er:YAG 2940 nm laser with SMA module was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Assessment of SD treatment using Er:YAG laser combined with light‐emitting diode red light (LED‐RL) treatment and an application of recombinant fibroblast growth factor showed a histological increase in elastic tissue and a significant improvement of stretch marks in all the treated 30 patients [17]. Recently, Meningaud et al [18] used Er:YAG laser (2940 nm) with SMA technology to treat SD and demonstrated an increase in volume and textural appearance of SD with minimal reported side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of SD treatment using Er:YAG laser combined with light‐emitting diode red light (LED‐RL) treatment and an application of recombinant fibroblast growth factor showed a histological increase in elastic tissue and a significant improvement of stretch marks in all the treated 30 patients [17]. Recently, Meningaud et al [18] used Er:YAG laser (2940 nm) with SMA technology to treat SD and demonstrated an increase in volume and textural appearance of SD with minimal reported side effects.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there is no universally accepted treatment against SD, and particularly, in the late stages, effective treatment has been found to be more difficult and unsatisfactory [6]. Several treatment options have been described for both SR and SA, including flashpumped 585-nm pulsed dye laser, intense pulsed light, 308-nm excimer laser, nonablative 1450-nm diode laser, radiofrequency device, 1064-nm Nd:YAG laser, nonablative fractional photothermolysis, ablative fractional CO 2 resurfacing, fractional radiofrequency microneedling, and fractional Er:YAG laser [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Cosmetic laser treatments, such as the pulsed‐dye laser and carbon dioxide (CO 2 ) laser, or other rejuvenation procedures, have also been developed and recommended [6]. However, because these treatments could not provide cosmetically satisfactory effects, several attempts have been made to increase their efficacy through combination therapy, including laser treatment, use of topical agents (such as epidermal growth factor), and novel technology [7–10].…”
Section: Introductionmentioning
confidence: 99%